(untitled) - Stuart T Smith (Switzerland, 1992)
This book provides bridge for those moving from either an ingineering or physics background towards the unique challenges offered by ultraprecision mechanisms. In providing a guide to basic techniques and much vital technical, analytical and practical information
Keywords: machine design,mechanical movement